Analysis of Strengthening of Soil Subsidence on Land in Tanjung Priok - Wahyudi Efendi, Aco (Yayasan Pendidikan Insan Mulia Utan Sumbawa, 2022)
Land subsidence is land subsidence in a vertical direction with respect to a specific elevation reference surface, such as B. Mean Sea Level (MSL) or a reference ellipsoid area. Subsidence is a natural phenomenon that often occurs in built-up areas, such as large cities that sit on top of a layer of sediment. This analysis assesses the stability and integrity of the building and obtains parameters in unstable areas and it is hoped that data will be available that can represent the soil conditions and their relevance to development. Also information about the effects of changes in the field due to development, such as e.g. B. Ground stability, and awareness of the possibility of excessive ground subsidence which may adversely affect the structure of the building above. The results of the decrease from tests on geoelectric trajectories with loading according to the construction conditions gave a decrease value of 6.78-7.8 cm, with the largest stress analysis on the ground 1000-1200 kN/m2 in the deepest soil layer at an altitude of 1000- 1200kN/m2 is -20-25m. Chemichal (epoxy resin) reinforcement method can inhibit the subsidence rate by 0.20 meters against the subsidence analysis results of 0.24 meters. The reinforcement method using compaction grouting can inhibit the subsidence rate by 0.21 meters versus the subsidence analysis results of 0.24 meters.